Transparent Active Matrix Organic Light-Emitting Diode Displays Driven by Nanowire Transistor Circuitry - Ju, Sanghyun; Li, Jianfeng; Liu, Jun; Chen, Po-Chiang; Ha, Young-geun; Ishikawa, Fumiaki; Chang, Hsiaokang; Zhou, Chongwu; Facchetti, Antonio; Janes, David B; Marks, Tobin J (Nano letters, 2008)
Optically transparent, mechanically flexible displays are attractive for next-generation visual technologies and portable electronics. In principle, organic light-emitting diodes (OLEDs) satisfy key requirements for this applicationtransparency, lightweight, flexibility, and low-temperature fabrication. However, to realize transparent, flexible active-matrix OLED (AMOLED) displays requires suitable thin-film transistor (TFT) drive electronics. Nanowire transistors (NWTs) are ideal candidates for this role due to their outstanding electrical characteristics, potential for compact size, fast switching, low-temperature fabrication, and transparency. Here we report the first demonstration of AMOLED displays driven exclusively by NW electronics and show that such displays can be optically transparent. The displays use pixel dimensions suitable for hand-held applications, exhibit 300 cd/m2 brightness, and are fabricated at temperatures suitable for integration on plastic substrates.